2011
DOI: 10.1007/s10803-011-1290-1
|View full text |Cite
|
Sign up to set email alerts
|

The Autism-Spectrum Quotient—Italian Version: A Cross-Cultural Confirmation of the Broader Autism Phenotype

Abstract: The Autism Spectrum Quotient (AQ) has been used to define the 'broader' (BAP), 'medium' (MAP) and 'narrow' autism phenotypes (NAP). We used a new Italian version of the AQ to test if difference on AQ scores and the distribution of BAP, MAP and NAP in autism parents (n = 245) versus control parents (n = 300) were replicated in a Sicilian sample. Parents of children with autism spectrum conditions scored higher than the control parents on total AQ, social skills and communication subscales, and exhibited higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
114
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 47 publications
14
114
0
2
Order By: Relevance
“…This supported previous work carried out by the same research group reporting significantly reduced social responsiveness in the siblings of autistic probands compared to a clinical control group (Constantino et al 2006). Research studies have also reported elevated scores on the 'social skills' subscale of the Autism-Spectrum Quotient in the parents of children with autism compared to parents of typically developing children; this was especially true for fathers Ruta et al 2011). Likewise, using the Communication Checklist-Adult Version, parents of children with autism reported significantly higher scores on the subscale 'social engagement' (i.e.…”
Section: Reciprocal Social Interactionsupporting
confidence: 88%
See 1 more Smart Citation
“…This supported previous work carried out by the same research group reporting significantly reduced social responsiveness in the siblings of autistic probands compared to a clinical control group (Constantino et al 2006). Research studies have also reported elevated scores on the 'social skills' subscale of the Autism-Spectrum Quotient in the parents of children with autism compared to parents of typically developing children; this was especially true for fathers Ruta et al 2011). Likewise, using the Communication Checklist-Adult Version, parents of children with autism reported significantly higher scores on the subscale 'social engagement' (i.e.…”
Section: Reciprocal Social Interactionsupporting
confidence: 88%
“…An additional study conducted by the same research group found associations between the same two combined subscales of the AutismSpectrum Quotient in fathers and children scoring low on the Children's Communication Checklist-2 (Bishop 2003;Bishop et al 2006). Similar findings have also been reported using large sample sizes by Wheelwright et al (2010) and in a cross-cultural validation study of the BAP using clinical and non-clinical samples from Italy (Ruta et al 2011). In both studies, the parents of children with autism scored significantly higher than a control group for difficulties on the communication subscale of the Autism-Spectrum Quotient.…”
Section: Language and Communicationsupporting
confidence: 67%
“…What is inherited is not necessarily clinically diagnosable ASD, but a broad phenotype that is characterised by a symptom continuity ranging from typicality to autism. This explains why the disorder itself is not often observed in family members, whereas sub-clinical characteristics are (Bishop et al 2004;Ruta et al 2012;Ruzich et al 2016;Wheelwright et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess these autistic traits, the autism spectrum quotient, AQ, was developed to observe whether the conditions of the autism spectrum extend to relatives of autistic individuals and to the general population ( Baron-Cohen et al 2001). Th e adult AQ has been widely used, and its reliability has been shown across diff erent times ) and cultures Ruta et al 2012;Hoekstra et al 2008). Studies have revealed that AQ scores diff erentiate parents of children with an Autism Spectrum Disorder (ASD) from control parents on social skills, communication, imagination, attention-switching, and total AQ subscales (Bishop et al 2004;Ruta et al 2012;Wheelwright et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Th e adult AQ has been widely used, and its reliability has been shown across diff erent times ) and cultures Ruta et al 2012;Hoekstra et al 2008). Studies have revealed that AQ scores diff erentiate parents of children with an Autism Spectrum Disorder (ASD) from control parents on social skills, communication, imagination, attention-switching, and total AQ subscales (Bishop et al 2004;Ruta et al 2012;Wheelwright et al 2010). Moreover, the AQ demonstrates high heritability (Hoekstra et al 2007).…”
Section: Introductionmentioning
confidence: 99%